Membekali Diri Untuk Menghadapi Fenomena Post-truth - Nita S Mudawamah (IJAL (Indonesian Journal of Academic Librarianship), 2018)
Right now we are dealing with a post-truth phenomenon. The phenomenon where people believe more in something that by their belief is right even though it is not in accordance with the facts The rise of information about hoaxes and fake news makes people unable to distinguish between accurate information and wrong information, between fiction and nonfiction, as if the boundaries of truth and errors are blurred. Donald Trump's victory and Ahok's defeat in political contestation is an example that we are in an era of post-truth. Social media has a significant contribution to the formation of the post-truth era. Public opinion formed through social media is stronger than the press based on facts and data. This article aims to provide an understanding of the post-truth phenomenon, also illustrates how to equip yourself to deal with this post-truth phenomenon.